Impact of replacing Chinese ethnicity‐specific fetal biometry charts with the INTERGROWTH‐21st standard. (14th September 2016) - Cheng, YKY; Leung, TY; Lao, TTH; Chan, YM; Sahota, DS
Abstract : Objective: To assess the impact of adopting the INTERGROWTH‐21 st biometry standards in a Chinese population. Design: Retrospective cohort study. Setting: A teaching hospital in Hong Kong. Population: A total of 10 527 Chinese women with a singleton pregnancy having a second‐ or third‐trimester fetal anomaly or growth scan between January 2009 and June 2014. Methods: Z ‐scores were derived for fetal abdominal circumference (AC), head circumference (HC), and femur length (FL) using the INTERGROWTH‐21 st and Chinese biometry standards. Pregnancies with aneuploidy, structural or skeletal abnormalities, or that developed pre‐eclampsia were excluded. Z ‐scores were stratified as <2.5th, <5th, <10th, >90th, >95th, or >97.5th percentile. Birthweight centile, adjusted for gestation and gender, was categorised as ≤3rd, 3rd to ≤5th, 5th to ≤10th, and >10th. Pairwise comparison and the McNemar test were performed to assess biometry Z ‐score differences and concordance between the INTERGROWTH‐21 st and Chinese standards. Main outcome measures: The sensitivity of both the local and INTERGROWTH‐21 st AC standards to identify pregnancies that were small‐for‐gestational‐age (SGA) was assessed. Results: INTERGROWTH‐21 st AC, HC, and FL Z ‐scores were significantly lower than those obtained using our local reference for AC, HC, and FL ( P < 0.0001 for all). The proportion of fetuses with biometry in the <2.5th, <5th, <10th, >90th, >95th, or >97.5th percentiles was statistically significant ( P < 0.01 for all). A total of 1224 (15.5%) of the scans at 18–22 weeks of gestation had AC, HC, or FL below the 3rd percentile of the INTERGROWTH‐21 st standard. Conclusions: Adopting the INTERGROWTH‐21 st standard would lead to a significant number of fetuses being at risk of misdiagnosis for small fetal size, particularly when using HC and FL measures. Tweetable abstract: INTERGROWTH‐21 st biometry assessment in Chinese leads to fetuses being at risk of misdiagnosis of small fetal size. Tweetable abstract: INTERGROWTH‐21 biometry assessment in Chinese leads to fetuses being at risk of misdiagnosis of small fetal size.